Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3846/jbem.2021.14729
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Work-Life Balance on the Relationship Between Work Culture and Employee Well-Being

Abstract: This article tends to fill the existing knowledge gap in understanding if work-life balance (WLB) can not only make a direct impact on employee well-being, but also play a mediating role between work culture and well-being. The purpose of this study was to investigate the mediating effect of WLB on the relationship between the structural dimensions of work culture – temporal flexibility, supportive supervision and operational flexibility – and employee well-being. The data were collected on the basis of a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Previous studies have also proven that employees' WLB has a significant positive impact on innovative behavior (Arifin et al, 2021 ). The role of WLB as a mediator in organizational factors is important for practitioners seeking to improve their organization's performance (Stankviciene et al, 2021 ). Haar et al ( 2017 ) finds that WLB mediates the impact of servant leadership on work engagement.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Previous studies have also proven that employees' WLB has a significant positive impact on innovative behavior (Arifin et al, 2021 ). The role of WLB as a mediator in organizational factors is important for practitioners seeking to improve their organization's performance (Stankviciene et al, 2021 ). Haar et al ( 2017 ) finds that WLB mediates the impact of servant leadership on work engagement.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…There are new findings that can be used as a reference in the development of subsequent research, where in previous studies it is still rarely carried out, namely the impact of WLB on QWL and the role of QWL partial mediation on the influence of WLB on JS. For example, 1) further research could explore the role of work culture as a mediation of the influence of WLB on employee well-being at work (Stankevičienė et al, 2021); 2) Further research can explore the role of QWL in mediating WLB compliance in work engagement (Rebecca et al, 2020). Further research can examine the influence of WLB and JS on employee performance (Abdirahman et al, 2018); (Thakur & Sharma, 2019); or assessing the impact of QWL on organizational excellence (Dayana & Nadarajan, 2019), organizational commitment (Risla & Ithress, 2018), and organizational performance (Al-Shawabkeh & Hijjawi, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Yun (2019) found that employees' WLB has a positive impact on their IWBs in the Chinese hotel industry. Hence, we predict that employees organizational performance (Stankevičiene et al, 2021). Haar (2013) finds that the impact of family conflict and enrichment on employees' achievement and wellbeing outcomes was mediated by WLB.…”
Section: Work-life Balance and Innovative Work Behaviormentioning
confidence: 92%